2003
DOI: 10.1063/1.1542930
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale strain field and In atom distribution in multiple quantum wells InGaN/GaN

Abstract: We present an atomic-scale structural and compositional analysis of ultrathin layers in multiple quantum well InGaN/GaN, by high-angle annular dark field (HAADF) scanning transmission electron microscopy (STEM). A high-quality HAADF STEM image processed by two-dimensional smoothing and deconvolution provides precise atomic-column positions and clear contrast, thereby allowing us to map the strain field and In atom distribution in successive GaN and InGaN layers. We conclude from these maps that there is a loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…In order to clarify the effect of indium concentration on growth and optical properties, a reliable and highly accurate determination of indium concentration in In x Ga 1-x N will be required. As Narukawa et al [4] suggested in 1997, transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDXS) techniques can be used to determine the localization of excitons at deep traps originating from In-rich regions in the quantum wells [5], however, due to the image observed in TEM being essentially a result of averaging through the thickness of the sample, a quantitative determination of the indium composition is difficult to obtain from conventional TEM [2]. In order to solve this problem, we have combined a self-consistent iterative procedure developed for EDXS in TEM with plasmon energy measurements by electron energy-loss spectroscopy (EELS).…”
Section: Introductionmentioning
confidence: 99%
“…In order to clarify the effect of indium concentration on growth and optical properties, a reliable and highly accurate determination of indium concentration in In x Ga 1-x N will be required. As Narukawa et al [4] suggested in 1997, transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDXS) techniques can be used to determine the localization of excitons at deep traps originating from In-rich regions in the quantum wells [5], however, due to the image observed in TEM being essentially a result of averaging through the thickness of the sample, a quantitative determination of the indium composition is difficult to obtain from conventional TEM [2]. In order to solve this problem, we have combined a self-consistent iterative procedure developed for EDXS in TEM with plasmon energy measurements by electron energy-loss spectroscopy (EELS).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported elsewhere 10,18-25 that HAADF images are sensitive to strain defects as well as to compositional variations in many different systems. In Si and other semiconductor doped systems, [18][19][20]22 it has been reported that strain fields surrounding dopant atoms may be the dominant source of contrast in HAADF images. [18][19][20]22 For B especially, it is known that there is a great tetrahedral misfit factor in relation to Si ͑ = 0.254͒, which results in a large amount of induced strain in the Si lattice around the doped zones with active B dopants.…”
Section: Discussionmentioning
confidence: 99%
“…In Si and other semiconductor doped systems, [18][19][20]22 it has been reported that strain fields surrounding dopant atoms may be the dominant source of contrast in HAADF images. [18][19][20]22 For B especially, it is known that there is a great tetrahedral misfit factor in relation to Si ͑ = 0.254͒, which results in a large amount of induced strain in the Si lattice around the doped zones with active B dopants. This atomic displacement caused by the substitutional B atoms distorts the neighboring Si lattice, which enhances the number of quasielastic scattering events and thereby produces the higher intensity observed.…”
Section: Discussionmentioning
confidence: 99%
“…Dots on the QWs emphatically indicate local lattice-strained spots as diffraction contrast. Watanabe et al 21) found In-rich spots, considered as quantum dots, 22,23) in the In 0:2 Ga 0:8 N (2.5) nm/GaN (8 nm) MQW. The In rich spots were distributed on the QWs and agreed to the areas with lattice expansion along the c direction.…”
Section: Resultsmentioning
confidence: 99%